A receptor domain controls the intracellular sorting of the ferrichrome transporter, ARN1 - Kim, Youngwoo (2005)
The Saccharomyces cerevisiae transporter Arn1p takes up the ferric-siderophore ferrichrome, and extracellular ferrichrome dramatically influences the intracellular trafficking of Arn1p. In the absence of ferrichrome, Arn1p sorts directly to the endosomal compartment. At low concentrations of ferrichrome, Arn1p stably relocalizes to the plasma membrane, yet little to no uptake of ferrichrome occurs at these low concentrations. At higher concentrations of ferrichrome, Arn1p cycles between the plasma membrane and endosome. Arn1p contains two binding sites for ferrichrome: one site has an affinity similar to the K(T) for transport, but the second site has a much higher affinity. Here we report that this high-affinity binding site lies within a unique extracytosolic, carboxyl-terminal domain. Mutations within this domain lead to loss of ferrichrome binding and uptake activities and missorting of Arn1p, including a failure to relocalize to the plasma membrane in the presence of ferrichrome. Mutation of phenylalanine residues in the cytosolic tail of Arn1p also lead to missorting, but without defects in ferrichrome binding. We propose that the carboxyl terminus of Arn1p contains a receptor domain that controls the intracellular trafficking of the transporter.